Copper Resistance in Aspergillus nidulans Relies on the PI-Type ATPase CrpA, Regulated by the Transcription Factor AceA - Antsotegi-Uskola, Martzel; Markina-Iñarrairaegui, Ane; Ugalde, Unai (Frontiers in Microbiology, 2017)
Copper homeostasis has been extensively studied in mammals, bacteria and yeast, but it has not been well documented in filamentous fungi. In this report, we investigated the basis of copper tolerance in the model fungus Aspergillus nidulans. Three genes involved in copper homeostasis have been characterized. First, crpA the A. nidulans orthologue of Candida albicans CaCRP1 gene encoding a PI-type ATPase was identified. The phenotype of crpA deletion led to a severe sensitivity to Cu+2 toxicity and a characteristic morphological growth defect in the presence of high copper. The expression pattern of crpA showed an initial strong elevation of mRNA and a low continuous gene expression in response to long term toxic copper levels. CrpA displayed some promiscuity regarding metal species response. Coinciding with maximum protein expression level peak, CrpA was localized close to the cellular surface, however protein distribution across diverse organelles suggests a complex regulated trafficking process. Secondly, aceA gene, encoding a transcription factor was identified and deleted, resulting in an even more extreme copper sensitivity than crpA mutants. Protein expression assays corroborated that AceA was necessary for metal inducible expression of CrpA, but not CrdA, a putative metallothionein which function has yet to be elucidated.